Rubella Virus- and Cytomegalovirus-Associated Anterior Uveitis: Clinical Findings and How They Relate to the Current Fuchs Uveitis Syndrome Classification - Yermalitski, Anton; Rübsam, Anne; Pohlmann, Dominika; Metzner, Sylvia; Pleyer, Uwe (Frontiers in Ophthalmology, 2022)
Rubella virus (RV) and cytomegalovirus (CMV) have both been inflicted with anterior uveitis (AU). Clinical phenotypes can vary widely among both entities and Fuchs uveitis syndrome (FUS) is one very distinct phenotype, that has been associated with either RV or CMV. The Standardization of Uveitis Nomenclature (SUN) Working Group recently updated the classification criteria for FUS with unilateral AU and either heterochromia or diffuse iris atrophy with stellate keratic precipitates as key criteria. Aim of this study was to determine whether our patients adhere to clinical diagnosis of FUS as previously reported and whether RV or CMV associated uveitis can be differentiated by clinical findings. Therefore, this study investigated the clinical characteristics of patients with AU and intraocular presence of either RV or CMV determined by Goldmann-Witmer coefficient (GWC). Our study included 100 patients (107 eyes) with AU and positive GWC for RV (86) and CMV (21). Clinical findings of RV positive eyes were keratic precipitates (91.9 %) with a predominantly diffuse distribution (81.4 %), unilateral cataract (80.2 %) or pseudophakia (73.5 %) and vitreous cells (59.7%), whereas heterochromia was present in only 39.5 % and iris atrophy in 12.9 % of all eyes. In CMV positive eyes, conversely, a higher incidence of ocular hypertension with markedly increased intraocular pressures above 30 mmHg (66.7 %), keratic precipitates (81.0 %), distributed most commonly in the center of the cornea (63.6 %), an unaffected lens (55.0 %), absent iris atrophy (100 %), and absent posterior synechiae (90.5 %) were dominant findings. A clinical presentation, that was mainly compatible with Posner-Schlossman syndrome. In our cohort of RV positive FUS patients, we saw a different cluster of clinical findings compared to the classification criteria suggested by the SUN Working Group. Main criteria such as unilaterality were mostly fulfilled. When applying all classification criteria only 8.4 % of the 107 eyes or 10.5 % of the RV positive eyes would qualify for the diagnosis of FUS. In addition, in our cohort there is even less evidence that CMV infection is related to FUS in a predominant Caucasian population.